Synthesis of YBa2Cu3O(7-δ) and Y2BaCuO5 nanocrystalline powders for YBCO superconductors using carbon nanotube templates. - Shi,Y; Hasan,T; Babu,NH; Torrisi,F; Milana,S; Ferrari,AC; Cardwell,DA (ACS Nano, 2012)
We fabricate nanosized superconducting YBa(2)Cu(3)O(7-δ) (Y-123) and nonsuperconducting Y(2)BaCuO(5) (Y-211) powders using carbon nanotubes as template. The mean particle size of Y-123 and Y-211 is 12 and 30 nm, respectively. The superconducting transition temperature of the Y-123 nanopowder is 90.9 K, similar to that of commercial, micrometer-scale powders fabricated by conventional processing. The elimination of carbon and the formation of a high purity superconducting phase both on the micro- and macroscale is confirmed by Raman spectroscopy and X-ray diffraction. We also demonstrate improvement in the superconducting properties of YBCO single grain bulk samples fabricated using the nanosize Y-211 powder, both in terms of trapped field and critical current density. The former reaches 553 mT at 77 K, with a ∼20% improvement compared to samples fabricated from commercial powders. Thus, our processing method is an effective source of pinning centers in single grain superconductors.